Randomized Efficacy Trial of Conventional, TCM Herb, and TEAS on Bone Marrow Suppression in Patients with Small Cell Lung Cancer after Initial Chemotherapy. (2nd February 2021) - Zhao, Fangchao; Wang, Zengying; Gao, Yanlin; Wu, Yusi; Liu, Jianming; He, Shuangliang
Abstract : Objective . To compare the efficiency of transcutaneous electrical acupoint stimulation (TEAS) with those of conventional and TCM herb on bone marrow suppression in small cell lung cancer (SCLC) patients after initial chemotherapy. Methods . We recruited 139 participants with pathologically confirmed SCLC who had not received chemotherapy. The conventional group ( n  = 37) received gemcitabine and cisplatin chemotherapy and routine care. The TCM herb group ( n  = 35) received 3 Diyushengbai tablets thrice a day for one day prior to chemotherapy and maintained during the trial. The TEAS group ( n  = 42) received TEAS at a frequency of 65–100 Hz with a pulse width of 100–200 μ sec. Acupoints were selected from Dazhui (DU14), Geshu (BL17), Zusanli (ST36), Sanyinjiao (SP6), and Hegu (LI4) and were treated on days 1, 2, 3, 5, 8, 14, 21, and 28 of chemotherapy for 30 min each day. All three groups underwent a 28-day treatment for a total of one treatment course. Changes in the white blood cell, neutrophil, platelet, and hemoglobin indices on day 1 before chemotherapy and days 5, 8, 11, 14, 21, and 28 days after chemotherapy were compared among the groups. Comfort levels of patients on day 1 before chemotherapy and days 5, 11, and 21 after chemotherapy were observed. Results . Compared with the conventional group, the white blood cell counts in the TEAS group on days 8 (7.07 ± 2.11 vs. 5.97 ± 2.10 × 10 9 /L) and 14 (6.14 ± 1.51 vs. 5.07 ± 2.41 × 10 9 /L) of chemotherapy and that in the TCM herb group on day 14 (6.63 ± 3.44 vs. 5.07 ± 2.41 × 10 9 /L) of chemotherapy were increased (P < 0.05 ). Compared with the conventional group, the neutrophil count in the TEAS group on days 5 (4.28 ± 1.54 vs. 3.01 ± 1.41 × 10 9 /L), 8 (3.75 ± 1.21 vs. 2.77 ± 1.17 × 10 9 /L), 11 (3.46 ± 1.31 vs. 2.31 ± 1.24 × 10 9 /L), 14 (3.18 ± 1.29 vs. 2.07 ± 1.14 × 10 9 /L), and 21 (4.67 ± 1.31 vs. 3.58 ± 1.23 × 10 9 /L) of chemotherapy and that in the TCM herb group on day 5 (3.88 ± 1.05 vs. 3.01 ± 1.41 × 10 9 /L) of chemotherapy were increased (P < 0.05 ). Compared with the conventional group, the platelet count of patients in the TEAS group increased on days 5 (264.7 ± 64.1 vs. 201.0 ± 55.7 × 10 9 /L), 8 (251.3 ± 74.9 vs. 188.2 ± 65.8 × 10 9 /L), 11 (236.7 ± 74.9 vs. 181.3 ± 84.3 × 10 9 /L), and 14 (238.3 ± 75.9 vs. 192.8 ± 95.8 × 10 9 /L) of chemotherapy (P < 0.05 ). Compared with the TCM herb group, the platelet count in the TEAS group increased on days 5 (264.7 ± 64.1 vs. 216.3 ± 57.9 × 10 9 /L), 8 (251.3 ± 74.9 vs. 213.7 ± 70.3 × 10 9 /L), 11 (236.7 ± 74.9 vs. 181.3 ± 84.3 × 10 9 /L), and 21 (254.8 ± 81.8 vs. 213.9 ± 82.6 × 10 9 /L) of chemotherapy (P < 0.05 ). Compared with the conventional group, the hemoglobin level in the TCM herb group increased on day 14 (135.03 ± 28.06 vs. 122.09 ± 12.63 g/L) of chemotherapy (P < 0.05 ). Compared with the conventional group, the comfort score of the TEAS group increased on days 5 (78.31 ± 10.21 vs. 70.18 ± 9.34 score) and 11 (80.07 ± 10.44 vs. 72.11 ± 9.47 score) of chemotherapy (P < 0.05 ). Conclusion . TEAS is an effective and safe treatment modality for improving bone marrow suppression in SCLC patients after initial chemotherapy. TEAS improved comfort levels more effectively than did conventional and TCM herb.